1991
DOI: 10.1128/mcb.11.6.3163
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dispersed spontaneous mutations: a novel pathway of mutation in a malignant human cell line.

Abstract: We analyzed the nature of spontaneous mutations at the autosomal locus coding for adenine phosphoribosyltransferase in the human colorectal carcinoma cell line SW620 to establish whether distinctive mutational pathways exist that might underlie the more complex genome rearrangements arising in tumor cells. Point mutations occur at a low rate in aprt hemizygotes derived from SW620, largely as a result of base substitutions at G-C base pairs to yield transversions and transitions. However, a novel pathway is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…Rather, it predicts that a clonal population of cells with known mutations at one gene would have a higher probability for the occurrence of second-site mutations than a randomly chosen group of clones. This hypothesis is supported by the observation that multiple mutations sometimes occur in the same gene in cancer cells (5,11). Furthermore, we have presented preliminary evidence for the occurrence of secondsite mutations at several VNTR (variable number of tandem repeat) loci (20).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Rather, it predicts that a clonal population of cells with known mutations at one gene would have a higher probability for the occurrence of second-site mutations than a randomly chosen group of clones. This hypothesis is supported by the observation that multiple mutations sometimes occur in the same gene in cancer cells (5,11). Furthermore, we have presented preliminary evidence for the occurrence of secondsite mutations at several VNTR (variable number of tandem repeat) loci (20).…”
supporting
confidence: 67%
“…The methods for the growth and maintenance of TK6 human lymphoblastoid cells have been described previously (10,21). Briefly, they were maintained in suspension culture at 37°C in a humidified 5% CO2 atmosphere in RPMI 1640 growth medium supplemented with 10% heat-inactivated horse serum and 1% penicillinstreptomycin (Gibco Laboratories, Grand Island, N.Y. Microtiter dishes were then scored for positive wells after 11 and 18 days of incubation with selective medium to identify both normal and slow-growth mutants (36). Positive wells were marked, and randomly chosen mutant clones, one from each parent culture, were transferred to 1 ml of fresh medium in 24-well dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen radicals produced in response to copper ions have been shown to induce both single and double transition mutations in a bacterial system (25), but such a mechanism is also inadequate to explain the results reported here; the copperinduced mutations had no apparent specificity for methylated or CpG sites, and the double mutations were all at tandem bases. Error-prone DNA synthesis has been invoked to explain multiple spontaneous mutations found both in shuttle vector systems and in the adenine phosphoribosyltransferase gene of a human carcinoma cell line (12,21), but in contrast to those described here, the mutations attributed to replication errors were more varied in type and spacing and showed no preference for CpG sites. Because the Cys-332 and Trp-334 mutations are at CpG sites, we favor a mechanism that attributes them to deamination of 5-Me-C residues; since hydrolytic deamination cannot explain their linked occurrence at high frequency, we postulate a deaminating enzyme whose activity is somewhat precessive along the DNA.…”
Section: Discussioncontrasting
confidence: 43%
“…In 1991, Harwood et al (35) found 4 cases of multiple mutations in the APRT gene of a cultured human colorectal carcinoma cell line. Possible mechanisms for the creation of these multiple mutations were speculated to be an imbalance in the deoxyribonucleotide triphosphate pool or mistakes in long patch repair such as mismatch repair (35,36). The high incidence of identical base substitutions in a single gene (Table 2) might be explained by an imbalance of one kind of deoxyribonucleotide triphosphate pool during DNA replication.…”
mentioning
confidence: 99%